Chemical strengthening method for glass raw sheet, low warpage value strengthened glass, cover glass and display

By combining wet and dry ion exchange chemical strengthening methods, the problem of warping of cover glass during chemical strengthening is solved in the floating process, and reinforced glass with high pressure stress and low warping values ​​is realized, which is suitable for mobile displays and other applications.

CN116924699BActive Publication Date: 2025-04-18河北视窗玻璃有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310951176.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-31
Publication Date
2025-04-18
Estimated Expiration
2043-07-31

AI Technical Summary

Technical Problem

During the chemical reinforcement process of cover glass produced by the float process, due to the inconsistent composition on both sides of the glass, the ion exchange rate is uneven, causing the glass to warp, affecting its performance in applications such as mobile displays.

Method used

A chemical strengthening method of glass original sheet is adopted, including the binding step of wet ion exchange and dry ion exchange. First, the preheated glass original sheet is placed in molten salt for wet ion exchange, and then the wet ion exchange glass original sheet is directly subjected to dry ion exchange, and finally annealing is performed.

Benefits of technology

Through this method, it is possible to significantly reduce the warpage value while ensuring that the glass has higher pressure stress after strengthening, and improve the mechanical strength and service performance of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004368466160000061
    Figure BDA0004368466160000061
  • Figure BDA0004368466160000071
    Figure BDA0004368466160000071
Patent Text Reader

Abstract

This invention relates to the field of chemical strengthening of glass, specifically a method for chemically strengthening glass sheets, low-warpage strengthened glass, cover glass, and displays. The chemical strengthening method for glass sheets provided by this invention includes the following steps: S1) placing a preheated glass sheet in molten salt for wet ion exchange; S2) subjecting the glass sheet after wet ion exchange in step S1) to dry ion exchange; S3) annealing the glass sheet after dry ion exchange in step S2). Compared with traditional methods, this invention adds a dry ion exchange step, thereby making the glass sheet less prone to warping during the chemical strengthening process, solving the problem of warping that easily occurs in existing strengthened glass manufacturing processes. Experiments show that the compressive stress on the glass surface obtained by this invention meets the standard, and the warpage value is reduced from 0.28 mm to 0.15 mm, a reduction of nearly 50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of glass chemical strengthening, in particular to a method for chemically strengthening a glass sheet, low-warpage value strengthened glass, cover glass and a display. Background Art

[0002] Chemical strengthening can improve the strength, scratch resistance and impact resistance of ultra-thin cover glass. The ultra-thin cover glass after chemical strengthening can meet the performance requirements of mobile displays such as mobile phones and tablets.

[0003] There are two production processes for cover glass: overflow method and float method. Due to the huge investment amount of overflow method, the production of cover glass original sheets on the market mainly adopts float method. The glass plate forming in the float production process is to flow the high-temperature molten glass on the molten tin liquid, and after flattening, polishing, thinning and cooling, it leaves the tin liquid and enters the annealing kiln. The whole process is completed on the surface of the tin liquid, and one side is in contact with the tin liquid (called tin side), and the other side is in contact with the protective gas (called air side), resulting in the inevitable diffusion of tin ions to the lower surface of the glass; finally, the finished glass shows different chemical compositions of the tin side and the air side, and both are different from the composition of the glass body. The difference in chemical composition of the tin side and the air side is an inherent problem of cover glass produced by the float process. Chemical strengthening of cover glass produced by the float process refers to immersing the glass in a molten salt (such as potassium nitrate) containing alkali metal ions with a larger radius than the alkali metal ions in the glass at a temperature not higher than the glass transition point (Tg), and ion exchange occurs between the glass and the molten salt, such as K in the molten salt. + Replacement of Na in glass + , K with large ionic radius + (0.133nm) replaced the Na + The space vacated by (0.099nm) causes "crowding" on the surface due to the volume difference between exchanged ions, forming surface compressive stress. When external force acts on this surface, this part of the compressive stress must be offset first, thus improving the mechanical strength of the glass and achieving the purpose of glass strengthening.

[0004] During the chemical strengthening process of float ultra-thin alkali-aluminosilicate glass, the inconsistent composition on both sides of the glass affects the ion exchange rate, making the CS (surface compressive stress) and DOL (ion exchange depth) on both sides of the cover glass inconsistent, causing the glass to bulge and warp toward the atmosphere side. This warping seriously affects the promotion of domestic ultra-thin alkali-aluminosilicate glass and its use by downstream customers. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a chemical strengthening method for a glass sheet, a low warpage value strengthened glass, a cover glass and a display. The chemical strengthening method provided by the present invention can strengthen the glass sheet to obtain a strengthened glass with high compressive stress and low warpage value.

[0006] The present invention provides a method for chemically strengthening a glass sheet, comprising the following steps:

[0007] S1) placing the preheated glass sheet in molten salt for wet ion exchange;

[0008] S2) performing dry ion exchange on the glass sheet after wet ion exchange in step S1);

[0009] S3) annealing the glass sheet after dry ion exchange in step S2).

[0010] The dry ion exchange of the present invention is specifically as follows: after the glass original sheet after wet ion exchange is completely taken out from the molten salt, it is directly kept warm without any treatment. At this time, the molten salt remaining on the surface of the glass original sheet will continue to perform dry ion exchange on the glass original sheet. The present invention has no special restrictions on the medium in which the glass original sheet is located during dry ion exchange, and it can be completely placed outside the molten salt; in certain embodiments of the present invention, after the glass original sheet after wet ion exchange is directly taken out from the molten salt, the glass original sheet after wet ion exchange is directly kept warm in the air without any treatment, that is, dry ion exchange is performed. The temperature of the dry ion exchange of the present invention is 360℃~450℃, preferably 370℃~440℃, more preferably 380℃~430℃, and more preferably 400℃~420℃; the time of the dry ion exchange is 0.1h~4h, preferably 0.3h~3h, more preferably 0.5h~2h, and more preferably 1h~1.5h.

[0011] The wet ion exchange of the present invention is a method of ion exchange of glass using molten salt in the process of glass chemical strengthening well known to those skilled in the art, and the preheated glass sheet is placed in the molten salt, specifically, the preheated glass sheet is completely placed in the molten salt. The temperature of the wet ion exchange of the present invention is 360℃~450℃, preferably 370℃~440℃, more preferably 380℃~430℃; the time of the wet ion exchange is 0.5h~8h, preferably 1h~7h, more preferably 2h~6h. The molten salt of the present invention is selected from alkali metal ion molten salt. In some embodiments, the molten salt is selected from at least one or two of potassium nitrate molten salt, sodium nitrate, and lithium nitrate. In other embodiments, the molten salt is selected from a mixed molten salt of 99.8% KNO3 and 0.2% NaNO3 by mass.

[0012] The inventors of the present application creatively discovered that by placing the original glass sheet after wet ion exchange in molten salt directly outside the molten salt for dry ion exchange, and replacing the traditional ion exchange with wet ion exchange and dry ion exchange in sequence, it is possible to ensure that the original glass sheet has a higher compressive stress after strengthening while having a lower warpage value. The present invention also optimizes the temperature and time during the wet ion exchange and dry ion exchange process, thereby further reducing the warpage value of the glass. The temperature of the wet ion exchange described in the present invention is not lower than the temperature of the dry ion exchange; the time of the wet ion exchange is not less than the time of the dry ion exchange.

[0013] The chemical strengthening method of the glass sheet provided by the present invention first places the preheated glass sheet in molten salt for wet ion exchange. Specifically, the present invention first preheats the glass sheet to obtain a preheated glass sheet, and then completely places the preheated glass sheet in molten salt for wet ion exchange. The preheating temperature of the present invention is 360℃~450℃, preferably 370℃~440℃, and more preferably 380℃~430℃; the preheating time is 1h~3h. The wet ion exchange of the present invention is the same as described above and will not be repeated.

[0014] In the present invention, the preheated glass sheet is subjected to wet ion exchange, and then the glass sheet after the wet ion exchange is subjected to dry ion exchange. The dry ion exchange of the present invention is the same as the above, and will not be described in detail.

[0015] The present invention performs dry ion exchange on the glass sheet after wet ion exchange, and then anneals the glass sheet after dry ion exchange to complete chemical strengthening of the glass sheet. The annealing temperature of the present invention is 360°C to 450°C, preferably 370°C to 440°C, and more preferably 380°C to 430°C; the annealing time is 2h to 4h.

[0016] The present invention provides a low warpage tempered glass, which is obtained by strengthening a glass sheet by the above-mentioned chemical strengthening method. In certain embodiments of the present invention, the low warpage tempered glass of the present invention has a size of 7 inches, and is obtained by strengthening a 7-inch glass sheet. The thickness of the low warpage tempered glass of the present invention is 0.1 mm to 2 mm, and the thickness of the glass sheet is the same as the thickness of the low warpage tempered glass finally obtained.

[0017] In certain embodiments of the present invention, the size of the low warp tempered glass of the present invention is 7 inches, and the warp value of the low warp tempered glass is 0.10mm to 0.15mm; the surface compressive stress (CS) value of the low warp tempered glass is 450MPa to 1000MPa, preferably 500MPa to 900MPa, and more preferably 550MPa to 800MPa. The stress layer depth (DOL value) of the low warp tempered glass of the present invention is 8μm to 60μm, preferably 10μm to 55μm, and more preferably 12μm to 50μm. The low warp tempered glass provided by the present invention not only has a compressive stress that can meet the use requirements, but also has a lower warp value.

[0018] In some embodiments of the present invention, the components of the glass raw sheet of the present invention include, by mass percentage of oxides: 62% to 73% SiO2; 4% to 13% Al2O3; 0.5% to 7.8% CaO; 4% to 11% MgO; 10% to 16% Na2O; and 0.5% to 3% K2O. In other embodiments of the present invention, the components of the glass raw sheet of the present invention include, by mass percentage of oxides: 58% to 73% SiO2; 8% to 18% Al2O3; 0.2% to 3% B2O3; 4% to 11% MgO; 10% to 20% Na2O; and 0.5% to 8% K2O. In one embodiment, the components of the glass raw sheet of the present invention include, by mass percentage of oxides: 69% SiO2; 5% Al2O3; 6.5% CaO; 4.5% MgO; 14% Na2O; and 1% K2O. In one embodiment, the components of the glass raw sheet of the present invention include, by mass percentage of oxides: 58% SiO2; 16% Al2O3; 1% B2O3; 5% MgO; 15% Na2O; and 5% K2O.

[0019] The present invention also provides a cover glass, which is prepared from the low warp value tempered glass. Since the low warp value tempered glass has a low warp value, it can be used as a cover glass in displays of various devices such as mobile phones, tablet computers and televisions. The present invention provides a display, which has the cover glass. The display of the present invention includes but is not limited to one or more of a mobile phone display, a tablet computer display and a television display.

[0020] The present invention provides a chemical strengthening method for a glass sheet, a low warpage strengthened glass, a cover glass and a display. The chemical strengthening method for a glass sheet provided by the present invention comprises the following steps: S1) placing the preheated glass sheet in a molten salt for wet ion exchange; S2) performing dry ion exchange on the glass sheet after the wet ion exchange in step S1); S3) annealing the glass sheet after the dry ion exchange in step S2). Compared with the three steps of preheating, ion exchange and annealing in the traditional chemical strengthening production, the strengthening method for the glass sheet of the present invention adds a dry ion exchange, so that the glass sheet is not easy to bend during the chemical strengthening process, and solves the technical problem that the glass is prone to warping in the existing glass chemical strengthening production process. Experiments show that the compressive stress on the glass surface obtained by the chemical strengthening method of the present invention can not only meet the needs of downstream customers, but also reduce the warpage value of 7-inch glass from 0.28mm to 0.15mm, that is, the warpage value is reduced by nearly 50%. DETAILED DESCRIPTION

[0021] The present invention discloses a method for chemically strengthening a glass sheet, a low warpage tempered glass, a cover glass and a display. A person skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the above. It should be particularly noted that all similar substitutions and modifications are obvious to a person skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0022] The glass sheets to be chemically strengthened used in Examples 1 to 3 and Comparative Examples 1 to 3 of the present application have a thickness of 0.7 mm and a size of 7 inches, and their components, calculated by mass percentage of oxides, include:

[0023] 69% SiO2; 5% Al2O3; 6.5% CaO; 4.5 MgO; 14% Na2O; and 1% K2O.

[0024] The glass sheet to be chemically strengthened used in Example 4 and Comparative Example 4 of the present application has a thickness of 0.7 mm and a size of 7 inches. Its components, calculated by mass percentage of oxides, include:

[0025] 58% SiO2; 16% Al2O3; 1% B2O3; 5% MgO; 15% Na2O; and 5% K2O.

[0026] The present invention will be further described below in conjunction with embodiments:

[0027] Example 1

[0028] (1) Preheating the glass sheet to be chemically strengthened in a preheating furnace at a temperature of 400° C. for 2 hours;

[0029] (2) The preheated glass sheet was completely immersed in molten salt (99.8% KNO3 + 0.2% NaNO3) for wet ion exchange at a temperature of 400°C for 2.5 hours;

[0030] (3) The glass sheet after wet ion exchange is taken out from the molten salt, and is directly subjected to dry ion exchange without any treatment, i.e., kept at a temperature of 400° C. for 1.5 hours;

[0031] (4) The glass sheet after dry ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain the chemically strengthened glass of the present invention.

[0032] Comparative Example 1

[0033] (1) Preheating the original chemically strengthened glass sheet in a preheating furnace; the preheating temperature is 400° C. and the time is 2 hours;

[0034] (2) immersing the preheated glass sheet in molten salt (99.8% KNO3 + 0.2% NaNO3) for wet ion exchange at a temperature of 400°C for 4 hours;

[0035] (3) The glass sheet after wet ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain conventional chemically strengthened glass.

[0036] The glasses obtained in Example 1 and Comparative Example 1 were subjected to performance tests and warpage value tests, as shown in Table 1:

[0037] Table 1

[0038]

[0039]

[0040] The surface compressive stress (CS) and stress layer depth (DOL) results of the two strengthening methods are similar. Although the surface compressive stress of the chemically strengthened glass of the present invention is slightly reduced, it can fully meet the needs of downstream customers. The warpage value of 7-inch glass is reduced from 0.28mm to 0.15mm, that is, the warpage value is reduced by nearly 50%, which is far better than the traditional chemically strengthened glass.

[0041] Example 2

[0042] (1) Preheating the glass sheet to be chemically strengthened in a preheating furnace at a temperature of 400° C. for 2 hours;

[0043] (2) The preheated glass sheet was completely immersed in molten salt (mass percentage: 99.8% KNO3 + 0.2% NaNO3) for wet ion exchange at a temperature of 420°C for 3 hours;

[0044] (3) The glass sheet after wet ion exchange is taken out from the molten salt, and without any treatment, dry ion exchange is directly performed, that is, the glass sheet is kept at a temperature of 420° C. for 1 hour;

[0045] (4) The glass sheet after dry ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain the chemically strengthened glass of the present invention.

[0046] Comparative Example 2

[0047] (1) Preheating the original chemically strengthened glass sheet in a preheating furnace; the preheating temperature is 400° C. and the time is 2 hours;

[0048] (2) immersing the preheated glass sheet in molten salt for wet ion exchange at a temperature of 420° C. for 4 hours;

[0049] (3) The glass sheet after wet ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain conventional chemically strengthened glass.

[0050] The glasses obtained in Example 2 and Comparative Example 2 were subjected to performance tests and warpage value tests, as shown in Table 3:

[0051] Table 2

[0052] Sample Comparative Example 2 Example 2 process Traditional chemical strengthening Chemical strengthening of the present invention Preheating temperature 400℃ / 2hrs 400℃ / 2hrs Ion Exchange / Wet Ion Exchange Conditions 420℃ / 4hrs 420℃ / 3hrs Dry ion exchange conditions none 420℃ / 1hrs Annealing temperature 400℃ / 2hrs 400℃ / 2hrs Surface compressive stress / MPa 723 642 Depth of stress layer / μm 14.8 14.3 Warpage value / mm 0.35 0.18

[0053] Example 3

[0054] (1) Preheating the glass sheet to be chemically strengthened in a preheating furnace at a temperature of 400° C. for 2 hours;

[0055] (2) The preheated glass sheet was completely immersed in molten salt (mass percentage: 99.8% KNO3 + 0.2% NaNO3) for wet ion exchange at a temperature of 380°C for 5 hours;

[0056] (3) The original glass sheet after wet ion exchange is taken out from the molten salt, and without any treatment, dry ion exchange is directly performed, that is, the glass sheet is kept at a temperature of 380° C. for 1 hour;

[0057] (4) The glass sheet after dry ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain the chemically strengthened glass of the present invention.

[0058] Comparative Example 3

[0059] (1) Preheating the original chemically strengthened glass sheet in a preheating furnace; the preheating temperature is 400° C. and the time is 2 hours;

[0060] (2) immersing the preheated glass sheet in molten salt for wet ion exchange at a temperature of 380° C. for 6 hours;

[0061] (3) The glass sheet after wet ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain conventional chemically strengthened glass.

[0062] The glasses obtained in Example 3 and Comparative Example 3 were subjected to performance tests and warpage value tests, as shown in Table 3:

[0063] Table 3

[0064] Sample Comparative Example 3 Example 3 process Traditional chemical strengthening Chemical strengthening of the present invention Preheating temperature 400℃ / 2hrs 400℃ / 2hrs Ion Exchange / Wet Ion Exchange Conditions 380℃ / 6hrs 380℃ / 5hrs Dry ion exchange conditions none 380℃ / 1hrs Annealing temperature 400℃ / 2hrs 400℃ / 2hrs Surface compressive stress / MPa 742 671 Depth of stress layer / μm 13.5 13.0 Warpage value / mm 0.30 0.16

[0065] Example 4

[0066] (1) Preheating the original chemically strengthened glass sheet in a preheating furnace; the preheating temperature is 400° C. and the time is 2 hours;

[0067] (2) immersing the preheated glass sheet in molten salt (mass percentage: 99.8% KNO3 + 0.2% NaNO3) for wet ion exchange at a temperature of 420°C for 4 hours;

[0068] (3) The glass sheet after wet ion exchange is taken out from the molten salt, and without any treatment, dry ion exchange is directly performed, that is, the glass sheet is kept at a temperature of 420° C. for 1 hour;

[0069] (4) The glass sheet after dry ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain the chemically strengthened glass of the present invention.

[0070] Comparative Example 4

[0071] (1) Preheating the original chemically strengthened glass sheet in a preheating furnace; the preheating temperature is 400° C. and the time is 2 hours;

[0072] (2) immersing the preheated glass sheet in molten salt (mass percentage: 99.8% KNO3 + 0.2% NaNO3) for wet ion exchange at a temperature of 420°C for 5 hours;

[0073] (3) The glass sheet after wet ion exchange is annealed at a temperature of 400° C. for 2 hours to obtain conventional chemically strengthened glass.

[0074] The glasses obtained in Example 4 and Comparative Example 4 were subjected to performance tests and warpage value tests, as shown in Table 4:

[0075] Table 4

[0076] Sample Comparative Example 4 Example 4 process Traditional chemical strengthening Chemical strengthening of the present invention Preheating temperature 400℃ / 2hrs 400℃ / 2hrs Ion Exchange / Wet Ion Exchange Conditions 420℃ / 5hrs 420℃ / 4hrs Dry ion exchange conditions none 420℃ / 1hrs Annealing temperature 400℃ / 2hrs 400℃ / 2hrs Surface compressive stress / MPa 842 801 Depth of stress layer / μm 43.3 42.8 Warpage value / mm 0.25 0.13

[0077] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for chemically strengthening a glass sheet, characterized in that: The following steps are involved: S1) placing the preheated glass sheet in molten salt for wet ion exchange; the temperature of the wet ion exchange is 360°C to 450°C, and the time of the wet ion exchange is 1 h to 8 h; S2) performing dry ion exchange on the glass sheet after the wet ion exchange in step S1); the temperature of the dry ion exchange is 360°C to 450°C, and the time of the dry ion exchange is 1 h to 4 h; the dry ion exchange is to place the glass sheet after the wet ion exchange in step S1) in the air without any treatment and directly keep it warm; S3) annealing the glass sheet after dry ion exchange in step S2); The temperature of the wet ion exchange in step S1) is not lower than the processing temperature of the dry ion exchange in step S2); The treatment time of the wet ion exchange in step S1) is not less than the treatment time of the dry ion exchange in step S2); The components of the glass sheet include, in terms of mass percentage of oxides: 62%~73% SiO2; 4%~13% Al2O3; 0.5~7.8% CaO; 4%~11% MgO; 10%~16% Na2O; and 0.5%~3% K2O; Alternatively, the components of the glass raw sheet include, in terms of mass percentage of oxides: 58%~73% SiO2; 8%~18% Al2O3; 0.2%~3% B2O3; 4%~11% MgO; 10%~20% Na2O; and 0.5%~8% K2O.

2. The method according to claim 1, characterized in that The preheating temperature in step S1) is 360°C to 450°C, and the preheating time is 1 h to 3 h.

3. The method according to claim 1, characterized in that The annealing temperature in step S3) is 360°C to 450°C, and the annealing time is 2 h to 4 h.

4. A low warpage tempered glass, characterized in that: The glass substrate is obtained by strengthening the glass substrate by the chemical strengthening method described in any one of claims 1 to 3.

5. A cover glass, characterized in that: The glass is prepared from the low warpage tempered glass as claimed in claim 4.

6. A display, characterized in that: The invention comprises the cover glass according to claim 5.

Citation Information

Patent Citations

  • Method for reducing warping in chemical strengthening of glass and jig for strengthening

    CN108516702A

  • Chemically toughened glass article having no optical orange skin and method for producing same

    CN112313182A